Prognostic value of secondary cardiac alterations in patients with moderate aortic valve stenosis. (14th October 2021) - Stoebe, S; Kandels, J; Metze, M; Lenk, K; Kuehne, C; Lavall, D; Laufs, U; Hagendorff, A
Abstract: Purpose: Echocardiographic characteristics that predict the progression of moderate aortic valve stenosis (mAS) are lacking. The aim of the present study was to evaluate the prognostic value of left ventricular hypertrophy (LVH), diastolic dysfunction (DD) and pulmonary artery hypertension (PAH) in patients with mAS. Methods: A total of 137 patients with asymptomatic mAS (age 72±10 years; females: 51 (37%); Blood Pressure: 143±21 / 78±13 mmHg) were included. Echocardiography was performed at baseline and at follow-up every six or/and twelve months. Patients with concomitant valvular defects, hypertrophic cardiomyopathy or chronic obstructive pulmonary disease were excluded. mAS was defined by current guideline criteria. Left ventricular ejection fraction (LVEF), LVH (LV mass index, males: >115g/m 2, females: >95 g/m 2 ), DD (E/e' >14) and PAH (maximum regurgitant velocity of tricuspid valve (TRVmax) >2.8m/s) were assessed. mAS patients were divided into 4 subgroups based on the number of secondary cardiac alterations: (0) no; (1) one; (2) two; (3) three cardiac alterations. The primary endpoint was progression to severe AS with indication for treatment (effective aortic orifice area (EOA) by continuity equation <1 cm 2 /<0.6 cm 2 /m 2 ) or the onset of symptoms. Results: mAS patients showed (0) no secondary cardiac alterations in 20% (n=28), (1) one in 40% (n=55), (2) two in 26% (n=35) and (3) three in 14% (n=19). Among mAS subgroups, no significant differences were observed for age and comorbidities. Echocardiographic parameters are summarised in Tab.1. In general, mAS patients with ≥ two cardiac alterations showed significantly smaller EOA ((0): 1.32±0.19 vs. 1.29±0.19, p>0.05; (1): 1.26±0.21 vs. 1.18±0.21, p>0.05; (2): 1.29±0.20 vs. 1.01±0.20, p<0.01; (3): 1.31±0.16 vs. 1.06±0.25, p<0.01) and higher mean pressure gradients (PGmean) ((0): 19.8±6.64 vs. 21.8±6.32, p>0.05; (1): 20.0±9.26 vs. 22.3±9.94, p>0.05; (2): 22.7±9.32 vs. 30.5±12.61, p<0.01 (3): 25.0±8.87 vs. 29.4±10.67, p<0.01) between baseline and follow-up (mean follow-up 20±9 months). Further, decrease of EOA/days was significantly higher in these patients ((0) −0.003; (1) −0.006; (2) −0.016; (3) −0.028; p<0.01, Fig. 1). As shown in Kaplan-Meier curve, mAS with ≥ two cardiac alterations showed rapid progression of moderate to severe AS (Fig. 2). Conclusions: In 40% of patients with mAS ≥ two secondary cardiac alterations (LV hypertrophy, DD and PAH) were observed. The presence of ≥ two of these secondary cardiac alterations is associated with rapid progression of mAS. FUNDunding Acknowledgement: Type of funding sources: None.